1983
DOI: 10.1002/qua.560230404
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and MO studies of hydroxy‐2‐aminotetralins

Abstract: Attempting to explain'the differences in the pharmacological profiles of the isomeric monohydroxyand dihydroxy-2-aminotetralins (DHAT) which are potent dopaminergic agonists we have calculated the conformational energies of 2-aminotetralin and its N,N-dipropyl derivative using the QCFF/Pi and PCILO methods. Molecular electrostatic potential (MEP) maps based on ab initio wave functions were computed for both dihydroxytetralins. Root-mean-square (rms) deviations from steric congruence between the enantiomeric $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The conformations of 2-aminotetralin derivatives have been studied by NMR,28 X-ray crystallography,29 and theoretical calculations. 30 The half-chair conformation for the cyclohexene portion of 2-aminotetralin derivatives is lower in energy than the half-boat conformation by 3-5 kcal/mol.30 The conformationally defined tyramine ana-logues 22-24 with a half-chair 2-aminotetralin moiety were better inhibitors of PNMT than were the conformationally defined half-boat 2-aminotetralin analogues 17-20. Apparently, the half-chair conformation for the 2-aminotetralin system is preferred by the enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conformations of 2-aminotetralin derivatives have been studied by NMR,28 X-ray crystallography,29 and theoretical calculations. 30 The half-chair conformation for the cyclohexene portion of 2-aminotetralin derivatives is lower in energy than the half-boat conformation by 3-5 kcal/mol.30 The conformationally defined tyramine ana-logues 22-24 with a half-chair 2-aminotetralin moiety were better inhibitors of PNMT than were the conformationally defined half-boat 2-aminotetralin analogues 17-20. Apparently, the half-chair conformation for the 2-aminotetralin system is preferred by the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the benzobicyclo[2.2.1]hept-2-ylamine (e.g. 17-21 and [30][31][32][33] and the benzobicyclo[3.2.1] octylamine (e.g. 22-25 and 34-36), we have used other conformationally defined benzobicyclic systems in our studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous NMR and X ray studies on 2-aminotetralin derivatives have shown that introduction of an amino substituent alters the symmetry of the tetralin aliphatic ring, producing up to eight different possible conformations. 12,13 It has been demonstrated that the half boat arrangement of the non aromatic region of 2-aminotetralin derivatives is lower in energy than the half chair conformation. 12, 14-16…”
Section: Insert Scheme 1 Herementioning
confidence: 99%
“…[12] [ 14-1 81). Dopaminergic compounds were also studied [ 191 [20]; thus the aromatic regions of 5,6-ADTN, 6,7-ADTN, and of the ergoline skeleton were compared, showing interesting similarities and differences. In the present study, we examine the electronic structure of the aromatic region of dopamine in various conformations.…”
mentioning
confidence: 99%